Numerical analysis of the torsional and flexural‐torsional buckling behaviour of compressed steel members at elevated temperature. Issue 2 (1st September 2021) - Possidente, Luca; Tondini, Nicola; Battini, Jean‐Marc
Abstract: Steel angle sections are frequently employed in bracing systems or in truss structures as single members or as built‐up members. Angles may be coupled back‐to‐back to create Tee or cruciform cross‐sections. These sections may be sensitive to torsional and flexural‐torsional buckling due to the cross‐section shape and the fact that the axial force may not be applied at the shear centre. In this work, a comprehensive numerical investigation of the behaviour of compressed angles, T and cruciform steel cross‐sections at elevated temperature was performed. A parametric study was carried out on Class 1 to 3 profiles subjected to uniform temperature distribution. Several numerical finite element analyses were carried out by varying the slenderness, the cross section, the steel grade and steel temperature employing beam and shell finite elements. It was found that the buckling curve given in the European structural code for steel structures in fire, i.e. EN 1993‐1‐2, provided results, that may not be conservative for a large slenderness range of practical interest, 0.4 ≤ λθ ≤ 1.5. Based on the results, adapted buckling curves were proposed to better predict the behaviour of angles, T and cruciform compressed cross‐sections at elevated temperature.